036 Mobile intraluminal long segment carotid thrombus causing ischaemic stroke. Issue 6 (24th May 2018) - Nham, Benjamin; Hawke, Simon
Abstract : Introduction: Mobile or free-floating long segment intraluminal thrombus within the carotid artery is a rare entity that has a high likelihood of causing recurrent ischaemic strokes if left untreated. There is no consensus about whether medical or surgical management of the carotid intraluminal thrombus represents the best management option. We present a case of an 83 year old man who presented with an ischaemic stroke secondary to this condition. Case: An 83 year old man presented to a regional hospital with acute right arm weakness and facial droop outside the timeframe for thrombolysis. CT carotid angiogram and carotid doppler showed non-occlusive mobile intraluminal thrombus involving a 3 cm segment of the vessel, just distal to the bifurcation. An MRI brain scan demonstrated an acute left MCA infarct. The patient declined carotid endarterectomy and was treated with intravenous heparin infusion. This was stopped one week later after he developed a thigh hematoma. Repeat CT angiogram revealed resolution of the thrombus and an underlying 30% non-calcific carotid plaque. He was treated with secondary prevention stroke agents. Management options of the mobile carotid thrombus include anticoagulation, commonly with intravenous heparin in the acute phase, or surgical management. It is unclear from the evidence which is superior. The literature suggests initial anticoagulation for 7–10 days resulted in a low rate of recurrent ischaemic events and that carotid revascularisation, if indicated, could later be safely performed or delayed if necessary. Conclusion: Mobile intraluminal carotid thrombus is a rare cause of ischaemic stroke. These mobile thrombi are often secondary to underlying ulcerated carotid plaques. In our case, medical management with intravenous heparin was a safe and effective treatment option with excellent functional recovery and resolution of the thrombus.